Analisis Progresif Skema Fundraising Wakaf dengan Pemanfaatan E-Commerce di Indonesia - Nely Rahmawati Zaimah (Institut Ilmu Keislaman Annuqayah, 2017)
There are many ways in waqf fundraising strategy. Internet utilization is a new platform that makes a global change in any line of economic terms. The new need for the provision of endowments and the understanding of the cash receipt ways will begin to be eroded. The ease of waqf transactions by using the internet and e-commerce sites in Indonesia is a new method although it has been used in many economic measures the long time ago. But there are some elements that really need a red line attention; product information, transaction cost charges, e-commerce company status, financing methods and accuracy in all sharia contexts and paradigm. Afterall, the entire hierarchy of waqf acquisition in waqf institutions that orbit digital transactions on commercial sites such as bukalapak, tokopedia and many others, ranging from fundraising, management to utilization, need to emphasize the systematic study of its conformity with sharia resolutions.